Guidance For Profiling Urban Displacement Situations: Challenges And Solutions. Joint IDP Profiling Service (Tufts Archival Research Center, 2018)
Guidance For Profiling Urban Displacement Situations: Challenges And Solutions. Joint IDP Profiling Service, by Karen Jacobsen and Ivan Cardona